2014
DOI: 10.1590/0102-33062014abb3510
|View full text |Cite
|
Sign up to set email alerts
|

Galling insects are bioindicators of environmental quality in a Conservation Unit

Abstract: Galls are well distributed across the World and among plant families. Their diversity can support the status of conservation of an area as an urban park, once inventories are presented. These inventories also help to understand the morphological patterns of the galls, based on their most common shape, color, host botanical families, inducers and galled organs. This study is about an inventory of galls at Parque Estadual Serra Verde, Brazil. This conservation unit is an urban park strongly anthropized in a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…In descending order, gall morphotypes appeared in Fabaceae (N = 11), followed by Euphorbiaceae (N = 7), Information about morphotype richness of other families and species is given in Table 2. Our results indicated that the richer the host family, the richer their gall morphotypes, corroborating data previously obtained in the Neotropical region (Gagné, 1994;Araújo, 2011;Santana & Isaias, 2014). However, it's important to highlight that of the 41 morphotypes sampled, 23 were found in the four host plant species: Copaifera langsdorffii, Croton floribundus, Diplopterys pubipetalum, and Bauhinia holophylla, with eight, seven, five and three morphotypes, respectively.…”
Section: Resultssupporting
confidence: 90%
“…In descending order, gall morphotypes appeared in Fabaceae (N = 11), followed by Euphorbiaceae (N = 7), Information about morphotype richness of other families and species is given in Table 2. Our results indicated that the richer the host family, the richer their gall morphotypes, corroborating data previously obtained in the Neotropical region (Gagné, 1994;Araújo, 2011;Santana & Isaias, 2014). However, it's important to highlight that of the 41 morphotypes sampled, 23 were found in the four host plant species: Copaifera langsdorffii, Croton floribundus, Diplopterys pubipetalum, and Bauhinia holophylla, with eight, seven, five and three morphotypes, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Leaves comprised the organ with the greatest richness of galls, corroborating the pattern observed in numerous other Brazilian ecosystems (e.g., Coelho et al 2009;Almada and Fernandes 2011;Maia 2013a, b;Maia and Souza 2013;Maia 2014;Santana and Isaias 2014). High gall richness on leaves may be explained by their high morphological plasticity and their roles as photosynthetic organs (Mani 1964;Formiga et al 2014;Maia 2014).…”
Section: Discussionsupporting
confidence: 77%
“…Maia [36], Maia and Fernandes [27], Santos et al [37], Silva et al [34], Fernandes et al [41], , Maia [29], Santana and Isaias [42].…”
Section: Protium Heptaphyllum Burseraceae 35mentioning
confidence: 99%